Long-term treatment with suberythropoietic epo is vaso- and neuroprotective in experimental diabetic retinopathy - Wang, Qian; Gorbey, Stefan; Pfister, Frederick; Höger, Simone; Dorn-Beineke, Andrea; Krügel, Katja; Berrone, Elena; Wu, Liang; Korff, Thomas; Lin, Jihong; Busch, Stephanie; Reichenbach, Andreas; et al. (Cellular physiology and biochemistry, 2011)
Background/Aims: Diabetic retinopathy is characterized by pericyte loss and vasoregression both in the clinic and in animal models. A mild neurodegeneration with loss of ganglion cells is also described in the diabetic retina. Like VEGF-A, Epo is angioprotective and, in high doses, neuroprotective, however, without affecting vessel permeability. This study was to investigate the effect of a long-term suberythropoietic dose of Epo on vascular damage and neurodegeneration in a rat model of diabetic retinopathy. Methods: We administered Epo 3x256 IU/kg body weight/week to streptozotocin-diabetic Wistar rats for up to 6 months. Leukostasis was analyzed by quantitation of CD45 positive cells adherent to the retinal microvasculature. VEGF-A levels were assessed by Elisa at 3 months of treatment. Vasoregression was quantified in retinal digest preparations after 6 months of Epo treatment. Neurodegeneration was analyzed from PAS stained retinal paraffin preparations. Results: Leukostasis was unaffected by treatment with Epo which significantly inhibited the loss of pericyte and the formation of acellular capillaries. Neurodegeneration in the diabetic retina was significantly reduced by Epo treatment. Increased VEGF-A levels in the diabetic retina were normalized by Epo treatment. Conclusions: Suberythropoietic Epo is effective to protect microvascular and neuronal damage in the experimental diabetic retina.